Luteinising hormone-releasing hormone nasal spray as therapy for undescended testicle. Issue 3 (March 1978) - Pirazzoli, P; Zappulla, F; Bernardi, F; Villa, M P; Aleksandrowicz, D; Scandola, A; Stancari, P; Cicognani, A; Cacciari, E
Abstract : Twenty-two prepubertal children with unilateral cryptorchidism were treated. None had undergone previous medical or surgical to modify the abnormal position of the testes, all of which were located inthe inguinal canal. Treatment was with luteinising hormone-releasing hormone (LH-RH) nasal spray given for 7 days. 9 boys insufflated 100 microgram LH-RH in each nostril 6 times per 24 hours (1200 microgram/24 h); the remaining 13 boys insufflated 500 microgram 12-hourly (1000 microgram/24 h). An LH-RH test (500 microgram IV) was carried out before and after therapy. Full descent of the testis into the scrotum was obtained in 7 out of the 22 cases; in a further 6 cases the testis moved down the inguinal canal. Basal values of luteinising hormone and follicle-stimulating hormone and those for pituitary reserve remained unchanged before and after therapy, and were similar to the values of a control group. No correlation was found between response to therapy and bone age, testosterone level in serum, basal values or pituitary reserve of luteinising hormone or follicle-stimulating hormone.